Agroecology for adaptation to climate change and resource depletion in the Mediterranean region. A review. (May 2020) - Aguilera, Eduardo; Díaz-Gaona, Cipriano; García-Laureano, Raquel; Reyes-Palomo, Carolina; Guzmán, Gloria I.; Ortolani, Livia; Sánchez-Rodríguez, Manuel; Rodríguez-Estévez, Vicente
Abstract: Mediterranean agriculture has coevolved with harsh environments and changing climate conditions over millennia, generating an extremely rich heritage of traditional knowledge; however, it is particularly threatened by climate change, including a higher than average warming and more frequent extreme climate events. The vulnerability is enhanced by the other components of global change affecting the Mediterranean basin, including biodiversity loss, freshwater overuse, disrupted nutrient cycles, soil degradation and altered fire regimes, in a context of high population density, water scarcity, high dependence on biomass and energy imports, and the prevalence of highly specialized, low diversity agroecosystems. Due to the need to create resilience to these interconnected threats, systemic adaptation measures are urgently needed. This review shows that this systemic approach can be provided by agroecology, which offers a holistic framework enabling the recovery and assessment of traditional knowledge and the cocreation of new local knowledge for enhancing resilience. It also highlights the role of the reconnection of food production and consumption, associated with the recovery of the locally-adapted, largely plant-based Mediterranean diet. Three types of complementary adaptation strategies for crop production are identified: (i) Biodiversity management to spread out risks and reduce pest damage; (ii) Increasing soil organic matter, e.g. with cover crops or crop varieties with higher residue and root production; (iii) Reducing fossil fuel dependence by avoiding synthetic chemicals, increasing efficiency and using renewable energy. Livestock adaptation strategies identified include: (i) management of extensive herds, including practices such as transhumance; (ii) diversification, use of local breeds and change of species; (iii) pasture and forage management, focusing on adjusting stocking rates to prevent abandonment and intensification, agroforestry, and fire management through grazing. Public policies must be set to tailor these strategies to each specific local situation with the involvement of all stakeholders and to establish or reinforce networks allowing knowledge exchange. Highlights: High vulnerability to climate change, global change and resource depletion Agro-food system level actions are needed to address the challenges Vast traditional ecological knowledge heritage could be used for adaptation Cropping systems adaptation by diversification, SOM management and renewable energy Livestock adaptation by agroforestry and fire management through grazing